Perbandingan Efektivitas Rebusan Air Jahe Dan Vitamin B6 Pada Ibu Hamil Trimester 1 Di Puskesmas Aur Duri Kota Jambi Tahun 2024 - Dewi Junita, Susilawati (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2024)
World Health Organization (WHO) the incidence of emesis gravidarum reaches 12.5% of the number of pregnancies in the world. Complaints of nausea and vomiting in emesis gravidarum are physiological things, but if these complaints are not treated immediately, they can become dangerous. The impact of nausea and vomiting that is not immediately resolved is Hyperemesis Gravidarum (excessive nausea and vomiting). This type of pre-experimental research design is one group pretest-posttest. The population of this study was all first trimester pregnant women as 30 pregnant women. The research sample was taken by using total sampling technique. Instruments used in PUQE. The statistical test used to analyze the data of the two variables is by using the T-test with a significance level of 5%. The results of the study before being given ginger water decoction, namely the average frequency of emesis gravidarum 12.60 and b6, namely 12.27. After being given a decoction of ginger water, it was 9.47 and after being given b6, it was 8.27. From the analysis, it can be concluded that consuming vitamin B6 gives a mean difference of 4, which means it is greater than the mean value of the ginger boiled water consumption intervention, which is 0.87. Midwives must be able to provide counseling on how to reduce nausea and vomiting, namely by giving ginger drink when experiencing emesis gravidarum, not only giving medicines to reduce nausea and vomiting